808 Frequency and impact of atherothrombotic status in patients undergoing transcatheter aortic valve replacement. (8th December 2021) - Boccuto, Fabiola; Sorrentino, Sabato; Carabetta, Nicole; Bellantoni, Antonio; Giordano, Salvatore; Cacia, Michele Antonio; Polimeni, Alberto; Leo, Isabella; Varano, Ylenia; Augusto, Florinda Maria; Mongiardo, Annalisa; De Rosa, Salvatore; et al.
Abstract: Aims: Many efforts have been made in the last decade to minimize the risk of bleeding in patients undergoing transcatheter aortic valve replacement (TAVR), such as a less intensive antithrombotic therapy and technical improvement in devices implantation. Conversely, evidence on high atherothrombotic status (HATR) is still lacking in patients undergoing TAVR. Accordingly, in this analysis, we aimed to evaluate frequency and impact of atherothrombotic status in patients undergoing transcatheter aortic valve replacement. Methods: Patients who underwent TAVR at our Institution from September 2008 to November 2020 were included in this analysis. Out of 407 patients, 6 (1.5%) were excluded as they underwent only balloon angioplasty or for procedural unsuccess. HATR status includes patients with prior percutaneous coronary intervention/coronary artery bypass graft, prior stroke/transient ischaemic attack (TIA), or with a diagnosis of diabetes. Continuous variables following normal distribution were compared with the student's t -test and categorical data were analysed with the chi-square test. A Cox regression model was used to evaluate the association between HART status and all-cause mortality at one 1-year follow-up. Results: Compared to patients with low atherothrombotic status (LATR) ( n  = 238; 59.4%), HART patients ( n  = 163; 40.6%) were older, more likely female and with a higher prevalence of common cardiovascular risk factors including chronic kidney disease, smoke, and hyperlipidaemia. Between LATR and HATR groups, no differences have been observed, in terms of procedural time, type of devices used (Balloon vs. self-expandable device), or hospitalization length. Compared to LART, HART patients were more likely to be discharged on statin (63.7% vs. 83%, P  < 000.1), on dual antiplatelet therapy (50.4% vs.58.9%, P  = 0.03), or on oral anticoagulant if required (27.7% vs. 29.5%, P  = 0.03). Furthermore, no differences have been observed in terms of in-hospital adverse events, including death, severe bleeding, any conduction disturbances requiring pacemaker implantation, access complications, myocardial infarction, or stroke/TIA. For instance, HART was not a predictor of mortality at 1 year follow-up, even after adjustment for baseline characteristics. Conclusion: In our population, no differences in procedural and in-hospital adverse events have been observed according to the atherothrombotic profile. HATR patients were more likely to be discharged with more intensive antithrombotic and hypolipidaemic strategies, despite the coexistent high prevalence of bleeding determinants. However, ATR status does not impact 1-year mortality even after adjustment for baseline characteristics.